Adaptation and validation of Social Media Use Integration Scale in Indonesian context: An exploratory and confirmatory factor analysis - Ardelia, Vania (Jurnal Psikologi, 2024)
Background: The growing popularity of social media has allowed people to be able to communicate in a more efficient and effective manner, as well as sharing any information in real time. Other numerous instruments were developed to measure individuals’ social media influence in their daily lives, but these have yet remained insufficient due to solely focusing on duration. Purpose: This study aims to examine the psychometric properties of the Social Media Use Integration Scale (SMUIS) for users of the Instagram platform in the Indonesia context. The scale was originally developed by Jenkins-Guarnieri et al. (2013) to measure how individuals integrate their social media usage with their social lives and psychological state.Method: This study used a sample of 305 participants (Male = 19.7%, Female = 80.3%) aged 18-29 years old (M = 21, SD = 3.15) which collected using purposive sampling method. Psychometric properties were analyzed using Exploratory Factor Analysis and Confirmatory Factor Analysis. Results contributed preliminary evidence of a satisfactory reliability and validity of the SMUIS in the Indonesian context. Implication: Further study should focus on testing the SMUIS on different age contexts and other social media platforms such as TikTok.